A comparative analysis of protected area expansion strategies for biodiversity and ecosystem services: a case study of Hainan Island - Wang, Lijuan (Frontiers in Ecology and Evolution, 2025)
IntroductionThe allocation of limited resources to simultaneously protect biodiversity and provide ecosystem services (ESs) is a critical global challenge in achieving the Kunming–Montreal Global Biodiversity Framework. One common strategy for this challenge is to expand existing protected areas (PAs), but the efficiency of different expansion methods for biodiversity and ESs remains unknown.MethodsThis study investigated two strategies, preserving existing PAs (“locking”) versus reassessing their boundaries (“unlocking”), to evaluate their effectiveness in achieving biodiversity and ES targets. The study used Marxan, a spatial modeling tool, to assess the effectiveness of PAs expansion strategies on Hainan Island in China.Results and discussionThe current PAs system, which encompasses 8.82% of the island, is inadequate for protecting the target levels of biodiversity and ES. We experimented with expanding the PAs to 15% using both strategies. The results revealed that, compared with the “unlocking” strategy, the “locking” strategy favored ES protection (66.49% vs 86.84%), but did so at the expense of biodiversity conservation. In contrast, the “unlocking” strategy required a larger area for expansion and led to increased habitat fragmentation compared wtih the “locking” approach. These findings underscore the need for a strategic approach to expanding PAs and balancing between biodiversity conservation and ES provision. This study offers valuable insights that could be used for broader applications in PAs management and biodiversity conservation planning.